Ultrasonography as a diagnostic tool for Neural Pain in Leprosy. - Clarissa Neves Spitz; Roberto Mogami; Izabela Jardim Rodrigues Pitta; Mariana Andrea Vilas Boas Hacker; Anna Maria Sales; Euzenir Nunes Sarno; Marcia Rodrigues Jardim (Public Library of Science (PLoS), 2022)
Leprosy is still a prevalent disease in Brazil, representing 93% of all occurrences in the Americas. Leprosy neuropathy is one of the most worrying manifestations of the disease. Acute neuropathy usually occurs during reaction episodes and is called neuritis. Twenty-two leprosy patients were included in this study. These patients had neural pain associated with ulnar sensory neuropathy, with or without adjunct motor involvement. The neurological picture began within thirty days of the clinical evaluation. The patients underwent a nerve conduction study and the demyelinating findings confirmed the diagnosis of neuritis. Ultrasonographic study (US) of the ulnar nerve was performed in all patients by a radiologist who was blinded to the clinical or neurophysiological results. Morphological characteristics of the ulnar nerve were analyzed, such as echogenicity, fascicular pattern, transverse cross-sectional area (CSA), aspect of the epineurium, as well as their anatomical relationships. The volume of selected muscles referring to the ulnar nerve, as well as their echogenicity, was also examined. Based on this analysis, patients with increased ulnar nerve CSA associated with loss of fascicular pattern, epineurium hyperechogenicity and presence of power Doppler flow were classified as neuritis. Therefore, patients initially classified by the clinical-electrophysiological criteria were reclassified by the imaging criteria pre-established in this study as with and without neuritis. Loss of fascicular pattern and flow detection on power Doppler showed to be significant morphological features in the detection of neuritis. In 38.5% of patients without clinical or neurophysiological findings of neuritis, US identified power Doppler flow and loss of fascicular pattern. The US is a method of high resolution and portability, and its low cost means that it could be used as an auxiliary tool in the diagnosis of neuritis and its treatment, especially in basic health units.